Molecular Detection the Agent that Causing Vaginitis in Vaginal Secretion from Women with Vaginitis and it Relation with Abortion (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
One hundred (100) swabs were collected from women with vaginitis ,from the hospital of Babylon city and private clinics. All the samples were taken from married women from pregnancy. The age of patient (17– 40) years. The sample was collected by disposable swabs .These swabs stored in freezing until were used, DNA was extracted from these swabs. The DNA genomic standard is prepared for the 16 S r RNA gene after the using of nanodrop spectrophotometer ( ng / ml ) for detection agent causing vaginitis by polymerase chain reaction technique .The result appeared that Candida albicans was more common in 79.17% while Trichomonas   in 22.92%, other causes were bacterial vaginosis. Also study the role of the infection agent with abortion, the result appeared that Megasphaera sp was high risk with abortion.